IOT-Enabled Human Presence Sensing For Automated Laboratory System - Anjali Raut; Mayuri Somdale; Nagma Tinwale; Atharv Chavare; Prajakta Jadhav; Samarth Kade; Nimisha Deval; Mahesh Mathpati (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
An IoT-based automation project leverages internet-connected devices to automate tasks and processes, enhancing efficiency, reducing costs, or improving safety. For instance, such a system can automate lighting, heating, and security in commercial buildings. The project design involves selecting appropriate sensors, actuators, and hardware components, alongside developing software to collect, analyze, and process data. A combination of cloud-based and local computing resources is used for data management and device control. Implementation includes installing and configuring hardware and software, followed by testing and debugging to ensure reliable performance. The system may also integrate with existing infrastructure, such as building management or enterprise resource planning systems. This automation enhances productivity, resource utilization, and decision-making, providing insights into operations for optimization. By streamlining processes and improving control, IoT-based automation projects enable organizations to achieve better performance and maintain a competitive edge in their respective industries